Perceived Discrimination and Religiosity among Young Refugees in Germany. Insights from a Longitudinal Study - Engel, Daniel; Penthin, Marcus; Pirner, Manfred; Riegel, Ulrich (Journal of Empirical Theology, 2025)
The article explores the relationship between religiosity and perceived discrimination among young refugees in Germany, focusing on a sample primarily composed of Muslim adolescents. Using data from a longitudinal study, the research investigates whether religiosity influences the perception of discrimination and how this relationship evolves over time. The results indicate a slight increase in perceived discrimination within one year, while levels of religiosity remained stable. Moreover, refugees who identify strongly with their religion experience higher levels of perceived discrimination. Religiosity, however, does not contribute noticeably to the increase of perceived discrimination over time. This finding deconstructs theories of coping which regard religiosity as powerful factor in dealing with discrimination. Therefore, this study contributes to postcolonial theory by offering empirical insights into the lived experiences of adolescent refugees in a society with lingering colonial-era structures.
CRIS-Team Scopus Importer:2025-05-30
Keywords: Muslim; Perceived Discrimination; quantitative data; Refugees; Religiosity